Embellishments from a Linguistic View: a Semiotic Analysis - Fatemeh Bahrami (مطالعات زبانی و بلاغی)
Embellishments count as one of the salient features of literary function of language and they have been studied over a long period of time in Persian literature. Nevertheless not much attention has been paid from a linguistic-semiotic perspective. The present paper aims at investigating some embellishments in Persian poems according to Saussure dealing with the following questions: 1- What aspects of Saussure’s viewpoint are adequate for explaining “pun”, “ambiguity”, “congeries” & “alliteration”? 2- Why does translation bleach aesthetical aspect of poems? To answer the first question, investigating the data reveals that aesthetic aspect of aforementioned embellishments follows from the interaction of neighboring signs in the chain, which simultaneously causes interfaces between syntagmatic and associative axes to represent various activated relations between present and absent signs, according to their similarities in signifiers, signified or both parts of the signs. Homonymy and polysemy are of vital importance to represent these similarities, especially in the case of ambiguity and pun. In alliteration and some other cases of pun the combination and linearity of signs in speech chain yields a secondary motivated signifier (and consequently, a corresponding signified) activated in the mind. Aesthetical aspect of congeries rests on the representation of a semantic field (congruence) in the syntagmatic axes. Indeed, various signs in the speech chain, which have some semantic features in common, cause associative similarity by compatibility among their signified. The answer to the second question relies on sign values and social aspect of language system.